Corruption "n" cure - Chitkara, M. G., 1932- (Delhi : A.P.H. Pub. Corp., 1997)
In the Indian context.
Includes bibliographical references (p. [167]-169) and index.
Momiul
Keywords: Misconduct in office -- India; Political corruption -- India; Business enterprises -- Corrupt practices -- India; Bribery -- India